ANALISIS PENGARUH CLINICAL AUTONOMY TERHADAP KEPUASAN KERJA DOKTER ERA JKN DI RSUD KOTA MAKASSAR - Andi Awaliya Anwar; Suci Rahmadani; Mega Marindrawati Rochka (VISIKES: Jurnal Kesehatan Masyarakat, 2019)
Services provided by medical personnel or doctors are an integral part of health services in hospitals, which have a very strategic position in efforts to improve the quality of service and satisfaction of consumers or patients who come to the hospital, which results in the satisfaction of the organization or the hospital itself . In connection with the age of BPJS implementation in Indonesia, the researchers are interested in exploring clinical autonomy (clinical autonomy) for the work satisfaction of doctors in the JKN era based on the transformation of fee for services into the INA CBGs package in hospitals. The purpose of this study was to determine the effect of clinical autonomy on doctors job satisfaction of JKN Era at Makassar City Hospital. This type of research is quantitative research with cross sectional research design. The population is all doctors in Makassar City Hospital as many as 35 people. Data analysis techniques using Spearman correlation analysis. The results showed that Control over work and Prerogative obtain need services affect job satisfaction in Makassar City Hospital (p = 0.012 and p = 0.035). From the results of the study concluded that clinical autonomy consisting of Control over work and Prerogative obtain need services affect the job satisfaction of doctors in Makassar City Hospital.It is recommended to the leadership of Makassar City Hospital to create better Control Over Work in terms of communication between doctors and management, so as to increase job satisfaction.